Pemerataan Hak Asasi Manusia (HAM) Terhadap Anak Panti Asuhan Insani Manuel - Anisa May Sarah Manalu; Sheilla Ananda; Siti Aminah Tanjung; Novry Ria Wani Damanik; Sahira Mutiara Tanjung; Siti Khadijah; Nurul Fadilah Lubis; Sri Rizky; Fazli Rachman (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Insani Manuel Orphanage plays an important role in ensuring equal distribution of Human Rights (HAM) for the children who live there. This research discusses concrete steps that can be taken to improve equal distribution of human rights in orphanages. Through a qualitative descriptive approach, the research wants to explore the challenges and opportunities in achieving equal access and opportunities for children at the Manuel Orphanage. Researchers use direct observation research methods with the technique of recording observation results and documenting them. Data collection was carried out using interviews and surveys in the field. Thus, the results obtained show that the implementation of equal distribution of human rights at the Insani Manuel Orphanage not only reflects a commitment to justice and equality, but also makes a positive contribution in making the nation's life smarter in accordance with the ideals of the Republic of Indonesia as stated in the 1945 Constitution.